2010
DOI: 10.1021/ct1002048
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Polarizability and the Effective Pair Potentials of Water

Abstract: Employing the continuum dielectric model for electronic polarizability, we have developed a new consistent procedure for parameterization of the effective nonpolarizable potential of liquid water. The model explains the striking difference between the value of water dipole moment μ~3D reported in recent ab initio and experimental studies with the value μeff~2.3D typically used in the empirical potentials, such as TIP3P or SPC/E. It is shown that the consistency of the parameterization scheme can be achieved if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
138
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(148 citation statements)
references
References 27 publications
10
138
0
Order By: Relevance
“…In this respect, it is interesting to note that three recent approaches for improving the description of ion-water interactions at the MM level rely in effect on a weakening of the ion-solvent Coulombic interactions. These are: the induction-type 66,67,104,107,[278][279][280][281]284 force fields, where CT effects are included explicitly, the molecular dynamics in electric continuum (MDEC) approach, [285][286][287] where the ion charge is effectively scaled 75,[77][78][79]288 by a factor of about 0.7-0.9 (in line with QM results 282 ), and the multisite ion description, [289][290][291][292][293][294][295] where the ion charge is redistributed over virtual off-center sites within the ion. The observation made here that the features of the QM/MM RDFs can be reproduced more accurately with a MM model when reducing the nominal charge of the ion to +0.75 e is perfectly in line with these considerations.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is interesting to note that three recent approaches for improving the description of ion-water interactions at the MM level rely in effect on a weakening of the ion-solvent Coulombic interactions. These are: the induction-type 66,67,104,107,[278][279][280][281]284 force fields, where CT effects are included explicitly, the molecular dynamics in electric continuum (MDEC) approach, [285][286][287] where the ion charge is effectively scaled 75,[77][78][79]288 by a factor of about 0.7-0.9 (in line with QM results 282 ), and the multisite ion description, [289][290][291][292][293][294][295] where the ion charge is redistributed over virtual off-center sites within the ion. The observation made here that the features of the QM/MM RDFs can be reproduced more accurately with a MM model when reducing the nominal charge of the ion to +0.75 e is perfectly in line with these considerations.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the arguments advanced in ref. [12][13][14][15], charge scaling would appear to be mandatory in models of ionic liquids without explicit polarization. In these systems, there is no high dielectric constant solvent to partially compensate for the effect of neglecting electronic polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Leontyev and Stuchebrukhovaa. [106][107][108] suggested that to describe the PES of salt solutions, the charge of the ions should be scaled by 1/ √ ǫ ∞ (i.e 1 √ 1.8 = 0.75) . This is an interesting suggestion.…”
Section: Bmentioning
confidence: 99%